2001
DOI: 10.1038/sj.onc.1204269
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic growth inhibition of prostate cancer cells by 1α,25 Dihydroxyvitamin D3 and its 19-nor-hexafluoride analogs in combination with either sodium butyrate or trichostatin A

Abstract: Prostate cancer is a major cause of male cancer death. In vitro and in vivo data support a role for 1a,25 Dihydroxyvitamin D 3 (1a,25(OH) 2 D 3 ) in regulating the growth and di erentiation of the normal prostate gland yet prostate cancer cells appear signi®cantly less sensitive to this action. Vitamin D 3 receptor (VDR) content or mutational status do not correlate clearly with the antiproliferative e ects of 1a,25(OH) 2 D 3 and therefore it is unclear why prostate cancer cell lines are signi®cantly less sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
82
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 54 publications
(47 reference statements)
2
82
0
Order By: Relevance
“…Still, the given data obviously look only at a very small portion of possibly involved pathways and thus have to be considered as preliminary. It cannot be ruled out that the observed changes could be a parallel issue as for example growth inhibition, induced by sodium butyrate, has been described in a cell line that has abrogated Rb function (Rashid et al, 2001). There might be other and potentially even more important structures such as cyclin A and D, p27 and protein kinase C, which are involved in the process of butyrate-induced growth inhibition (Chen et al, 2003;Kim et al, 2003;Siddiqui et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, the given data obviously look only at a very small portion of possibly involved pathways and thus have to be considered as preliminary. It cannot be ruled out that the observed changes could be a parallel issue as for example growth inhibition, induced by sodium butyrate, has been described in a cell line that has abrogated Rb function (Rashid et al, 2001). There might be other and potentially even more important structures such as cyclin A and D, p27 and protein kinase C, which are involved in the process of butyrate-induced growth inhibition (Chen et al, 2003;Kim et al, 2003;Siddiqui et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There might be other and potentially even more important structures such as cyclin A and D, p27 and protein kinase C, which are involved in the process of butyrate-induced growth inhibition (Chen et al, 2003;Kim et al, 2003;Siddiqui et al, 2003). Nevertheless, exploring the activation of p-21, including the role of Sp1 transcription factor, is a very promising approach (Wang et al, 2000;Rashid et al, 2001;Margueron et al, 2003), as this gene appears to be rarely mutated in common human malignancies in contrast to p53 (Terao et al, 2001). A similar pattern of mechanism has been described for several cell lines including prostate cancer cell lines for the effect of phorbol ester (Blagosklonny et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated that treatment of human prostate cancer cell lines with inhibitors of HDACs suppresses cell growth (11,12). Moreover, studies have indicated that inhibitors of HDACs differentially induce apoptosis in prostate cancer cells (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…They also block angiogenesis and stimulate immune system in vivo. 5,6 HDAC inhibitors have a selective toxicity against tumor cells and a synergistic activity with existing therapeutic agents, including retinoic acids, 7 vitamin D analogues 8 and peroxisome proliferator-activated receptor ligands. 9 A number of HDAC inhibitors are currently in phase I and II clinical trials (eg depsipeptide, AN-9: pivaloyloxymethyl butyrate), and encouraging results have been reported for their use in the treatment of both hematological malignancies and solid tumors.…”
Section: Introductionmentioning
confidence: 99%